Foregrounding the Verbal Process: A Corpus Stylistic Analysis of Adichie’s Zikora (2020) - Samuel Kwesi Nkansah; Emmanuel Mensah Bonsu (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
Literature mirrors societies. While the plethora of studies on African literature, spanning from the early 21st century, have discussed literary texts in their political spectrums, recent studies using transitivity analysis have offered new and objective understandings of these novels. Nonetheless, most transitivity analyses have been fixated on characterization, style and themes. Against this background, the purpose of this study was to use corpus procedures to examine the transitivity of verbal process types in Adichie’s recent novel Zikora. Assisted by corpus linguistics, the study used transitivity as an analytical framework to analyse the verbal process in the text. From the analysis, three major findings are reported from the discussion. First, through the verbal processes, the Adichie deconstructed the myriad suffering and subjugation of women through dialogic means and taking responsibility for their livelihood. Second, the foregrounded verbal processes reflect the attribution of processes to other characters than accounting for the literary effects projected through the clauses. Finally, while the writer used the projected clauses to attribute the verbal processes to others, the dominant use of the first-person mode of narration identifies a sharing of roles to account for the writing of the literary work. Following these findings, the study extends the scholarship on literary stylistics and provides implications for further research in other genres of (African) literature.